IMPLEMENTASI PENDEKATAN DEEP LEARNING DALAM PEMBELAJARAN BAHASA KELAS IV DI MIN 1 PURWAKARTA - Lutfi Amaliah, Nisa; Jahro, Nurdiatul; Rosmaladewi, Okke (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The deep learning approach in education emphasize meaningful learning that encourages deep understanding, critical thinking, and reflaction in students. This study aims to describe the iplementation of the deep learning approach in language learning among fourth-grade students in MIN 1 Purwakarta and to identify its impact on the learning process and outcomes of students. This study uses a qualitative apporoach with a descriptive method. Data collection techniques were carried out through learning observations, interviews with fourth-grade teachers, and documentation. The result showed that deep learning approach was implemented through contextual learning, reflective discussion, group work, and the integration of religious values in language learning. This implentation had a positive impact on improving students understanding of the material, their activeness, and their critical and communicative thinking skills. This the deep learning approach is effectively applied in language at MIN 1 Purwakarta